Bridging the digital disconnect: Exploring the views of professionals on using technology to promote young people's mental health. (August 2017) - Clarke, Aleisha M.; Chambers, Derek; Barry, Margaret M.
The increasing role of online technologies in young people's lives has significant implications for professionals' engagement with technologies to promote youth mental health and well-being. However, relatively little is known about professionals' views on the role of technologies in supporting youth mental health. This article outlines key findings from a needs assessment survey carried out in Ireland that sought to determine the views of professionals working with young people on the use of online technologies in supporting young people's mental health and well-being. A total of 900 professionals from across the education, health, and mental health professions completed an online survey. The findings demonstrate the importance of the internet as a resource for professionals working with young people, with over 98% of those surveyed expressing a readiness to use online resources to support young people's mental health. The nature of preferred online technologies differed according to professional groupings, however, 63% of overall respondents indicated they would look for help on a dedicated mental health website. Guidelines on working with young people and their parents on the promotion of positive mental were requested with the most frequency. Among the barriers identified were concerns about access to reliable information that was relevant to specific professional roles, and the need for organizational support of professionals' use of online evidence-based resources. Concerns were also expressed that online resources could replace face-to-face support services for young people, and the need for training professionals in their appropriate use. The results highlight the potential role of technology in assisting professionals through the provision of online training, reliable information, and practical resources on the promotion of positive youth mental health.